Wide-field Global VLBI and MERLIN combined monitoring of supernova remnants in M82 - Fenech, D.; Beswick, R.; Muxlow, T.; Pedlar, A.; Argo, Megan (Wiley-Blackwell Publishing Ltd., 2010)
From a combination of Multi-Element Radio-Linked Interferometer Network (MERLIN) and global Very Long Baseline Interferometry (VLBI) observations of the starburst galaxy M82, images of 36 discrete sources at resolutions ranging from ∼3 to ∼80 mas at 1.7 GHz are presented. Of these 36 sources, 32 are identified as supernova remnants, two are H ii regions and three remain unclassified. Sizes, flux densities and radio brightnesses are given for all of the detected sources. Additionally, global VLBI only data from this project are used to image four of the most compact radio sources. These data provide a fifth epoch of VLBI observations of these sources, covering a 19-yr time-line. In particular, the continued expansion of one of the youngest supernova remnants, 43.31+59.3, is discussed. The deceleration parameter is a power-law index used to represent the time evolution of the size of a supernova remnant. For the source 43.31+59.3, a lower limit to the deceleration parameter is calculated to be 0.53 ± 0.06, based on a lower limit of the age of this source.